2020
DOI: 10.1016/j.jtcme.2019.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Chrysin mitigated obesity by regulating energy intake and expenditure in rats

Abstract: Background and aim Chrysin is a flavonoid found in plant extracts from Passiflora species, honey and propolis. It has demonstrated anti-adipogenic activity in vitro but there are no studies substantiating the anti-obesity activity of chrysin in vivo . Experimental procedure The pancreatic lipase (PL) inhibitory potential of chrysin was determined by preliminary in silico … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Rats fed fructose over a long period gain weight and develop abdominal obesity (Tappy, 2018). In addition to that, feeding the rats with HFD increased the body weight of rats, BMI, AC/TC ratio, and adiposity index compared to the normal control group (Pai et al, 2020). Chronic fructose feeding renders animals leptin resistant.…”
Section: High-fructose Induced Hypertensionmentioning
confidence: 99%
“…Rats fed fructose over a long period gain weight and develop abdominal obesity (Tappy, 2018). In addition to that, feeding the rats with HFD increased the body weight of rats, BMI, AC/TC ratio, and adiposity index compared to the normal control group (Pai et al, 2020). Chronic fructose feeding renders animals leptin resistant.…”
Section: High-fructose Induced Hypertensionmentioning
confidence: 99%
“…85 In another study of rats fed a highfat diet containing chrysin (100 mg/kg) for 16 weeks, chrysin significantly attenuated weight gain, inhibited pancreatic lipase (a target of antiobesity drugs), and, quite interestingly, increased voluntary exercise. 86 Looking closely at these studies, it is clear that the majority of those in experimental animals used propolis extract, and the regions from which the propolis was harvested varied as well. Therefore, they have not properly validated the effects of propolis or the contributions of its components.…”
Section: Antiobesity and Antidiabetes Effects Of Propolismentioning
confidence: 99%
“…One such study showed that consumption of a high-fat diet containing CAPE (0.02%–0.5%) significantly reduced body weight and epididymal white adipose tissue weight in mice, and the authors presumed this effect was due to suppression of adipocyte differentiation . In another study of rats fed a high-fat diet containing chrysin (100 mg/kg) for 16 weeks, chrysin significantly attenuated weight gain, inhibited pancreatic lipase (a target of antiobesity drugs), and, quite interestingly, increased voluntary exercise …”
Section: Antiobesity and Antidiabetes Effects Of Propolismentioning
confidence: 99%
“…It also restores the level of serum lipids; counteracts lipid peroxidation and limits accumulation of hepatic triglycerides (172). Chrysin significantly reduces body weight, BMI, abdominal circumference-thoracic circumference ratio, calorie intake while increasing locomotor activity and fecal cholesterol excretion in obese rats fed highfructose diet compared to control (173). More interestingly, apigenin administered to high fatdiet induced obese mice, reduces both body weight and visceral adipose tissues, binding to nonphosphorylated STAT3 in visceral adipose tissues, thus reducing its transcriptional activity.…”
Section: Flavonoids Alleviate Obesitymentioning
confidence: 99%